Estrus Synchronization Protocols for Natural Service - Daniella Heredia; Angela Gonella-Diaza; Kalyn Waters (EDIS)
This publication is intended for producers interested in improving the reproductive efficiency and performance of their cows. This publication explains the process of estrus synchronization and the protocols that can be used for natural service synchronization. Written by Daniella Heredia, Angela Gonella-Diaza, and Kalyn Waters, and published by the UF/IFAS Department of Animal Sciences, February 2025.